Effect of Waiting Room Services and Facilities on Passenger Satisfaction at Komodo Labuan Bajo Airport - Nining Suharni; Hodi (Formosa Journal of Sustainable Research, 2023)
One of the endeavors to energize the advancement of air transportation is through the improvement of all frameworks and their supporting parts, including the traveler terminal. The air terminal structure is an interfacing part between land transportation modes and air transportation modes, should have the option to serve the quantity of traveler developments during top hours and with making arrangements for the drawn out period at Komodo Labuan Bajo Air terminal. The quantitative An investigation method that takes into account the way of thinking of positivism, which is utilized to look at a populace or test, the information is gathered with research instruments, the idea of the information examination is measurable/quantitative, the reason for which is to test the speculations that still up in the air and to do different tests comprising of legitimacy, ordinariness and furthermore utilizing the old style supposition test and t, f, and R2 tests, all of which will be completed by the specialist.We took a gander at X1 and X2 on Y and found that how great travelers and things they approach can influence how blissful they are. At the point when we take a gander at the information, we see that 79.6% of Y is impacted by X1 and X2, however 20.4% is affected by different things that we didn't study. We likewise find that X1 and X2 unequivocally affect Y, and that implies H3 is right